اختلاف المصادر وثمراته عند المحدثين والمستشرقين في السيرة النبوية (دراسة نموذجية ومقارنة ): The Method of Orientalists in Dealing with the Holy Prophet’s Biography - Dr. Ghulam Ahmad; Dr. Abdul Majeed Baghdadi (MEI, 2023)
This paper investigates the sources of the Holy Prophet’s Biography between the Traditionalists and the Orientalists. Discussing about Prophet’s Biography and its sources is one of the most important issues that, we must talk about because the right or wrong vision or theory is based on the sources of biography, so all we see the conflict between the Traditionalist and the Orientalists, therefore the present paper aims to compare the sources of biography followed by Traditionalist and Orientalists in terms of importance and order. The purpose of this paper is to expand the Prophet’s Biography, and knowledge of some stories about the biography of that time. Further, it explores contradictions in their views regarding Holy Prophet’s Biography. Thus the following sources have been consulted in order to explore the Prophet’s Biography such as, a). The original sources: the Holy Quran, the accurate Sunnah, the books of the Prophet's prophecies, evidence of prophecy and particular biography books, b). The supplementary sources are genealogical books, general historical books, literatures and poetry books, book of biographies, and knowledge of the narrators. Additionally, the sources of Orintalists have also been examined in order to find out contradictions in their views. Finally, the findings and suggestions have been mentioned with reference to the above mentioned sources.